Prolonged Febrile Seizures and their Management - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at Tel-Aviv Sourasky Medical Center, and three other medical centers in Israel, obtained data, prospectively, on all children presenting in the emergency departments from January 2008 to March 2010 with prolonged febrile seizures.